Análise de vibração aleatória em um veículo baja baseada em entrada PSD determinada experimentalmente - Roman, Ana Beatriz Matias (Universidade Federal de São Carlos, 2025)
Baja vehicles are a category of off-road vehicles designed to withstand adverse terrain conditions. In Brazil, the Society of Automotive Engineers (SAE) promotes regional and national Baja competitions, in which vehicles are developed by Brazilian universities. The chassis is a vehicle component whose purpose is to ensure driver safety and to support the other Baja subsystems within its structure. Currently, the roll cage is regulated to guarantee driver safety, restricting the combination of materials, as well as the diameter and thickness of the tubes that compose it (or materials with equivalent strength). Therefore, in order to understand the effects of impacts and vibrations to which a chassis is subjected, a modal analysis of the complete Baja vehicle of the Federal University of São Carlos (UFSCar) was performed, followed by vibration testing on the structure, enabling comparison with the developed computational model. Subsequently, the modal results were used in a spectral analysis of the roll cage by considering vibrational inputs originating from the ground, which were obtained through an experimental test. Thus, based on the results obtained, it was possible to analyze the dynamic behavior of the roll cage structure and to obtain parameters (reaction forces at the wheels) for the design of the vehicle suspension components.
Random vibration analysis of a baja vehicle based on experimentally determined PSD input
Keywords: Veículo baja; Instrumentação com acelerômetros; Processamento de sinais de aceleração; Análise de vibração aleatória; Baja vehicle; Accelerometer instrumentation; Acceleration signal processing; Random vibration analysis; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS; 9. Indústria, Inovação e Infraestrutura